SUSTANABILITY IN THE ONLINE EDUCATION: MORE SUSTANAIBLE FUTURE? - Silic, Mario; Leontic, Marijana; Hajdin, Marga (Global journal of Business and Integral Security, 2022)
Sustainability in online education is an important topic that has gained high importance in the last few years. How to achieve sustainable goals through online education is one of the key concerns for many educational institutions. Technology driven online education has bright future but further research is needed to better reposition the role and the future of online education within sustainable boundaries. New technologies (Virtual Reality, Augmented Reality, etc.) will try to jeopardize current campus based models in the same way that Covid19 pandemic has done. New research should aim at unveiling the success factors of the online education but at same time, keeping the campus based premises that mainly relate to quality indicators.